First records of Erysiphe corylacearum (Erysiphales, Ascomycota) on Corylus avellana in Ukraine - Heluta, V.P.; Makarenko, N.V.; Al-Maali, G.A. (Український ботанічний журнал, 2019)
Information on the records of a new adventive powdery mildew fungus Erysiphe corylacearum (Erysiphales, Ascomycota) in Ukraine is provided. The fungus was found on Corylus avellana (Betulaceae) in Kyiv, as well as in Crimea. Current distribution of this species outside its primary range is analyzed. It has been shown that the fungus came to Ukraine from the East through the Caucasus. Ukrainian specimens were compared with samples collected in the Far East of Russia. It was found that Ukrainian specimens have slightly larger chasmothecia, somewhat more numerous asci, which are slightly more elongated and often short stalked. It is noted that the fungus has a great invasive potential and in the future can cause considerable damage to the forestry of European countries. The article is illustrated with micrographs obtained under light and scanning electron microscopes. Наводиться інформація про знахідки в Україні нового адвентивного борошнисторосяного гриба Erysiphe corylacearum ( Erysiphales, Ascomycota). Гриб виявлено на Corylus avellana ( Betulaceae) у м. Києві, а також в Криму. Аналізується новітнє поширення цього виду поза межами його первинного ареалу. Показано, що гриб потрапив в Україну зі Сходу через Кавказ. Порівнюються українські матеріали зі зразками, зібраними на Далекому Сході Росії. Встановлено, що вони мають дещо більші хазмотеції, більшу кількість сумок, останні більш витягнуті, частіше на маленькій ніжці. Зазначається, що гриб має значний інвазійний потенціал і в майбутньому може завдавати помітної шкоди лісовому господарству європейських країн. Стаття проілюстрована зображеннями, отриманими за допомогою світлового та скануючого електронного мікроскопів.